Transformasi Pembelajaran Matematika: Dari Metode Tradisional ke Pendekatan Berbasis Teknologi (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This study aims to examine the changes in mathematics education from traditional methods to technology-based approaches through a Systematic Literature Review (SLR). The literature review involved selecting sources indexed in Google Scholar, ScienceDirect, DOAJ, Scopus, and SpringerLink, focusing on research published between 2014 and 2024. The study concentrates on trends, effectiveness, and challenges in the implementation of technology in mathematics education. Findings indicate that technologies such as Game-Based Learning (GBL), Augmented Reality (AR), and Learning Management Systems (LMS) significantly enhance student engagement and facilitate the understanding of complex mathematical concepts. Moreover, technology-based learning methods have been shown to improve student learning outcomes, particularly in critical thinking, creativity, and problem-solving skills. Nevertheless, the research also identifies several challenges, including limited access to technology, low digital literacy levels among teachers and students, and resistance to changes in teaching methods. The study underscores the importance of professional development for educators to optimally support the implementation of technology in the classroom. Overall, the transformation of mathematics education towards technology-based approaches demonstrates a positive impact on students. However, broader support is needed in terms of infrastructure, teacher training, and paradigm shifts in teaching methods to ensure the effective integration of technology in various educational contexts